Cognitive and Affective Learning in English as a Foreign Language/English as a Second Language Instructional-Learning Contexts: Does Teacher Immediacy Matter? - Wang, Xiaoyan (Frontiers in Psychology, 2021)
A noteworthy frame of literature has maintained the idea that communication in the classroom is dominant in language education and in the process of language learning, teachers as an important figure may apply several ways to develop interpersonal relationships and social manners, namely teacher immediacy that has been established to support affective and cognitive learning in instructional settings. Therefore, the present theoretical review tries to systematically refocus on the existing literature about teacher immediacy and its types, nonverbal and verbal, and their significant connections with affective and cognitive education. To this end, the present review focuses on social behavior to review the eminence of teacher immediacy in the classroom and unquestionably exemplify their relationship with affective and cognitive learning. As a final fact, this review has been intended to consider the prevailing literature about teacher behavior, and correspondingly suggestions and recommendations have been presented for language teaching stakeholders in the educational setting.